Pyrrolizidine Alkaloids of Senecio sp from Peru - Vasquez, LR (2011)
This work was supported by a Collaborative Research Grant from CSIC-CONCYTEC, National University of the Peruvian Amazonia, Iquitos, Peru, Ministerio de Educacion y Ciencia, Spain (CTQ2009-14629-C02-01) and a predoctoral MAEC-AECID fellowship to L. R. Vasquez.